Pemanfaatan Limbah Klobot Jagung Menjadi Produk Ekonomi Kreatif: Upaya Pemberdayaan Masyarakat Desa Simbar Waringin, Lampung - Ika Trisnawati Alawiyah; Agus Setiawan; Miftahunnisa’ Igiriza; M. Alwi; Intan Saravina (CV. BImbingan Belajar Assyfa, 2026)
Agricultural waste, such as corn husks, often presents an environmental problem and remains underutilized. This community service initiative aimed to empower community organizations in Simbar Waringin Village, Central Lampung, by transforming corn husk waste into creative economy products. The activity employed the Asset-Based Community Development (ABCD) approach, encompassing stages of preparation, asset identification, program design, workshop implementation, and evaluation. The results indicated that the community successfully processed corn husks into various handicraft products, including ornamental flowers, woven bags, and souvenirs. This activity not only enhanced the skills and creativity of the participants but also strengthened solidarity among village organizations (PKK, Karang Taruna, and Farmers' Groups) and opened alternative economic opportunities. This waste utilization aligns with the principles of a circular and green economy, where environmental problems are converted into economic opportunities. Although marketing remains a challenge, the potential for product development and access to digital markets is wide open for the program's sustainability. In conclusion, community empowerment based on local potential is proven effective as a sustainable development strategy that integrates social, economic, and environmental aspects.